2020
DOI: 10.3389/fmicb.2020.01816
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Diversity of Natural Bacterial Communities in Mabisi, a Traditionally Fermented Milk

Abstract: Many traditionally fermented milk products such as mabisi involve spontaneous fermentation, which can result in bacterial community composition variation due to selection pressure. The aim of this study was to determine the composition of bacterial communities in the different types of mabisi produced across Zambia and identify the factors that influence their composition. Samples of mabisi were collected across the country, and analyzed for pH and bacterial communities using 16S rRNA amplicon sequencing. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
1
29
0
1
Order By: Relevance
“…Finally, our method only detects bacteria and not eukaryotes and viruses that are also part of the microbial community. We chose to focus on bacteria when describing effects of fermentation practice in levels of backslopping on microbial community dynamics since in previous work yeast were not found to be present at high abundance in Mabisi (Moonga et al 2020 ; Schoustra et al 2013 ). Future work could include an analysis of all microbes (including viruses) that form the community, as well as their functionality that determine product properties.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our method only detects bacteria and not eukaryotes and viruses that are also part of the microbial community. We chose to focus on bacteria when describing effects of fermentation practice in levels of backslopping on microbial community dynamics since in previous work yeast were not found to be present at high abundance in Mabisi (Moonga et al 2020 ; Schoustra et al 2013 ). Future work could include an analysis of all microbes (including viruses) that form the community, as well as their functionality that determine product properties.…”
Section: Discussionmentioning
confidence: 99%
“…e Alcaligenes têm sido identificados em leite cru refrigerado e derivados lácteos, porém normalmente não estão associados a produção de proteases. Entretanto, Pseudomonas é um gênero comumente associado à produção de enzimas líticas, sendo frequentemente isolado em leite cru refrigerado devido à sua capacidade de se multiplicar em temperaturas de refrigeração e de produzir biofilmes nos equipamentos de ordenha e armazenamento do leite (Moonga et al, 2020;Teh et al, 2014;Vithanage et al, 2016;von Neubeck et al, 2015;Zhang et al, 2020).…”
Section: Resultsunclassified
“…This work experimentally analyzed the microbial community composition before and after fermentation in traditional maize based fermented food Munkoyo [ 7 ]. Other previous studies showed that environmental selection of different pH did affect microbial community composition—this is work performed with Mabisi [ 8 ]. Thus, apparently, the selective forces of the fermentation environment have a great impact.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of sample exchange between producers, microbial ecosystems from the different producers evolve independently [ 6 ]. Previous work has shown that initial differences between microbial community structure at the start of a fermentation cycle does not significantly impact the final community structure [ 7 ], and that processing practice is an important driver of microbial community composition [ 8 ]. Work based on laboratory experiments has suggested that processing temperature is a key factor, which can drive microbial community composition [ 9 ].…”
Section: Introductionmentioning
confidence: 99%